2013
DOI: 10.1111/php.12123
|View full text |Cite
|
Sign up to set email alerts
|

Sunburn Risk Among Children and Outdoor Workers in South Africa and Reunion Island Coastal Sites

Abstract: To estimate potential sunburn risk for schoolchildren and outdoor workers, ground-based ambient solar ultraviolet radiation (UVR) measurements were converted into possible child (5% of ambient solar UVR) and outdoor worker (20% of ambient solar UVR) solar UVR exposures by skin type and season for three coastal sites: Durban, Cape Point (South Africa) and Saint Denis (Reunion Island, France). Cumulative daily ambient solar UVR levels were relatively high at all sites, especially during summer, with maximum valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…Interestingly, exposure of car guards as a percentage of ambient solar UVR at 24% was higher than the 20% hypothesized in an earlier study (26) albeit lower than the 84% (15) and 46% (25) reported before. Construction workers in Spain were found to receive a median of 13.9% of the total daily ambient solar UVR (13), and outdoor workers in a New Zealand study received 20.5% of the total daily available ambient solar UVR (12).…”
Section: Discussioncontrasting
confidence: 74%
“…Interestingly, exposure of car guards as a percentage of ambient solar UVR at 24% was higher than the 20% hypothesized in an earlier study (26) albeit lower than the 84% (15) and 46% (25) reported before. Construction workers in Spain were found to receive a median of 13.9% of the total daily ambient solar UVR (13), and outdoor workers in a New Zealand study received 20.5% of the total daily available ambient solar UVR (12).…”
Section: Discussioncontrasting
confidence: 74%
“…[13][14][15][16] This belief arose because outdoor workers are exposed to UV every day, unlike indoor workers, so that their skin acclimates by thickening the stratum corneum and by producing the pigment melanin (tan). However, contrary to this popular belief, outdoor workers can get numerous sunburns and can also experience blistering events [28][29][30][31] reviewed by Glanz. 32 For example, the study by Buller et al 30 found 45% of the ski area employees got sunburned and 8% received blistering sunburns.…”
Section: Discussionmentioning
confidence: 99%
“…25 UVB exposures of skin creates cutaneous vitamin D 3 production 26 that sunscreens dramatically reduce. 27 Furthermore, contrary to popular belief, outdoor workers get numerous sunburns [28][29][30][31] reviewed by Glanz.…”
Section: Introductionmentioning
confidence: 99%
“…Sunburn risks among children and outdoor workers were evaluated on Reunion Island and in South Africa. High values of cumulative daily ambient solar UV radiation were found for the three sites studied (Wright et al, 2013).…”
Section: Introductionmentioning
confidence: 94%